The Contribution of Brain-Derived Neurotrophic Factor (BDNF) and its TrkB Receptor to Hippocampal Neuron Resistance to Ischemia-Reperfusion (Experimental Study) - Irina V. Ostrova; Maria Sh. Avrushchenko; Arkady M. Golubev; Nataliya V. Golubeva (Общая реаниматология)
The purpose of the study: to assess the content of BDNF and its TrkB receptor in the populations of hippocampal pyramidal neurons in the post-resuscitation period and to identify the contribution of these factors to the neuron resistance to ischemia.Material and methods. The condition of populations of pyramidal neurons of the CA1 and CA4 hippocampus fields was investigated in white mature male rats that underwent a 10-minute cardiac arrest at different periods of the post-resuscitation period (1st, 4th, 7th, 14th day). Animals after a sham surgery served as a reference group. Immunocytochemical methods were used to determine immunoreactivity to BDNF and TrkB proteins. Based on the visual inspection and analysis of the optical density, the following types of neurons with different color intensity were distinguished: weak (BDNF–, TrkB–), moderate (BDNF+, TrkB+) and strong (BDNF++, TrkB++). The total density of neurons and the number of cells with different immunoreactivity to the studied proteins per 1 mm of length were determined. We used the Olympus BX-41 microscope and Image Scope M, ImageJ 1.48 v, MS Excel software. Statistical data processing was performed using Statistica 7.0 software.Results. There was a decrease in the overall density of the population of pyramidal neurons in both studied fields of the hippocampus of the resuscitated animals as compared to the reference group: in the CA1field, on the 4th day after cardiac arrest (26%); in the CA4 field, on the 7th day (38.5%). It was found that the number of BDNF+ neurons doubled in the CA4 field on the 4th day, and the number of BDNF++ neurons decreased. On the 7th day, the number of BDNF– cells decreased sharply, the number of BDNF+ cells decreased to the reference level, and the number of BDNF++ neurons remained reduced vs. the reference group. There was a decrease in the number of BDNF– and BDNF+ cells in the CA1 field on the 4th day, while the number of BDNF++ neurons remained the same. The observed changes remained on Day 14.The analysis TrkB protein expression in the CA4 field on the 7th day of the post-resuscitation period as revealed by reactivity with anti-TrkB antibody demonstrated a decrease in the number of TrkB– cells as compared to the reference group. By the 14th day, the number of not only TrkB– neurons, but also TrkB+ cells was reduced, while the number of TrkB++ neurons remained at the level of the reference group. There was a decrease in the number of TrkB+ neurons was observed in the CA1 field on the 4th day after resuscitation. On day 7, there was a decreased numbers of both TrkB+ and TrkB–-neurones. The number of TrkB–-neurones remained decreased up to day 14. At that, the number of TrkB++ neurons persisted at the reference level throughout the observation period.Conclusion. The obtained results demonstrate that the resistance of neurons to ischemia-reperfusion is associated with the intracellular expression of BDNF and TrkB proteins. The reduction of the overall density of neurons in the post-resuscitation period was obsereved both in hippocampal fields CA1 and СА4; only cells with minimal and moderate content of the studied proteins died. Neurons with the highest BDNF and TrkB protein content survived.